2012
DOI: 10.1166/jnn.2012.6582
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy Method to Differentiate Between Normal and Cancerous Breast Cells

Abstract: Attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) is used to find the structural differences between cancerous breast cells (MCF-7 line) and normal breast cells (MCF-12F line). Gold nanoparticles were prepared and the hydrodynamic diameter of the gold nanoparticles found to be 38.45 nm. The Gold nanoparticles were exposed to both MCF-7 and MCF-12F cells from lower to higher concentrations. Spectroscopic studies founds nanoparticles were within the cells, and increasing the nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In some cases, nanoparticles are used to introduce drugs into specific sites because they have a particularly good uptake within cells [64]. Another exciting application presented by Lane and Seo demonstrated that ATR FTIR spectroscopy can be used to distinguish between cancerous and benign cells containing gold nanoparticles [64].…”
Section: Surface Enhanced Infrared Absorption Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, nanoparticles are used to introduce drugs into specific sites because they have a particularly good uptake within cells [64]. Another exciting application presented by Lane and Seo demonstrated that ATR FTIR spectroscopy can be used to distinguish between cancerous and benign cells containing gold nanoparticles [64].…”
Section: Surface Enhanced Infrared Absorption Spectroscopymentioning
confidence: 99%
“…The presence of the nanoparticles within the cells allows an enhanced IR absorbance, similar to the effect seen when the surface is modified as described above. The study by Lane and Seo [64] shows the increase in spectral intensity with increasing gold nanoparticles concentration for cancerous and normal cell lines, which could allow for any spectral differences to be seen more easily. This development further emphasises the potential of ATR FTIR spectroscopy for medical diagnostics and is not limited by the reproducibility issues still present within SEIRAS studies.…”
Section: Surface Enhanced Infrared Absorption Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR requires only a small amount of sample for analysis with easy and quick preparation if necessary, and it allows automated and repetitive analyses, leading to nonsubjective evaluation of the sample [4,6,7]. Furthermore, ATR, the experimental configuration for FTIR spectra acquisition utilized in this study, presents high signal-to-noise ratio (SNR), does not present unwanted spectral contributions, and enables a sample to be analyzed without further preparation simply by placing it in direct contact with a crystal with a refractive index higher than the sample [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically for breast cancer, FTIR spectroscopy has been used for many purposes [15][16][17][18][19][20][21][22][23][24], mainly for detection [4,[25][26][27][28]. Most FTIR spectroscopy studies in breast cancer used normal breast tissue and breast tumors [4,[29][30][31], breast cell lines [11,32,33], and blood of breast cancer patients [25,27]. To our knowledge, there are no studies using ATR-FTIR spectroscopy for breast cancer diagnosis using saliva as the biological sample.…”
Section: Introductionmentioning
confidence: 99%